031 Managing rituximab delivery in a neurosciences centre. Issue 12 (14th November 2019) - Dorsey, R; Williams, T; Singh-Curry, V; Johnson, M; Pritchard, J; Muraro, P; Nicholas, R
Abstract : Rituximab has potential indications in neurology not as yet studied in RCTs making access difficult but also means that there is no coherent process to ensure useful outcome data is acquired. In addition alternatives such as immunoglobulins now have limited availability. We set up a multidisciplinary team (MDT) to establish appropriate indication for rituximab, and ensure consistency of administration and outcome data collection. Data from neurosciences in Imperial Healthcare NHS Trust was audited (6/2010–4/2018). After completing a systematic review a MDT was initiated with peripheral nerve, epilepsy, and neuroinflammatory experts. The MDT was then audited (4/2018–1/2019). 79 subjects were assessed: mean age 49.7±15.4 years (range 19–80yrs). 42 (5.4 per year) were treated since 2010 and 29 since the MDT began (34.8 per year). The commonest diagnoses were limbic encephalitis (17) and vasculitis (12). Subjects had on average 2.8 immune therapies prior to treatment. 21/71 had PLEX and 23/71 had immunoglobulins. Prior to the MDT inception 65% of subject reported positive outcomes. After the MDT 8 (19%) were rejected and there was minimal use in those without a clear diagnosis. Subjects who receive rituximab often have a series of in-hospital complex expensive therapies prior to treatment. A rituximab MDT increases its use in appropriate groups.